Effect of delayed sampling on umbilical cord arterial and venous lactate and blood gases in clamped and unclamped vessels. Issue 5 (25th April 2006) - Armstrong, L; Stenson, B
Abstract : Background: Cord blood lactate at birth is a marker of antenatal hypoxia, and is comparable to pH as a prognostic tool. Objective: To determine, by a prospective observational study, the effect of delayed sampling from arteries and veins that were double clamped to isolate the blood from the placenta (clamped), and from vessels that were not isolated from the placenta (unclamped). Methods: Paired samples taken from clamped and unclamped vessels at 0, 20, 40, and 60 minutes were analysed for lactate, base excess, pH, and Pco 2 . Data were analysed as the change from time 0 at 20, 40, and 60 minutes. Results: Thirty eight placentas of infants delivered by elective caesarean section were studied. Arterial samples were taken from 20 placentas, and venous samples from 18 placentas. Arterial and venous lactate was significantly higher than at time 0 by 20 minutes in both clamped and unclamped vessels. Changes in unclamped vessels were greater than in clamped vessels. The pH remained unchanged over 60 minutes in clamped vessels, but changed significantly in unclamped vessels. Base excess changed significantly in both clamped and unclamped vessels. Conclusions: Cord blood samples taken after 20 minutes delay are unreliable for lactate measurement, even if the vessel has been doubly clamped to isolate the blood from the placenta. Current guidelines that state that blood can be sampled from a clamped cord for up to one hour after delivery should not apply to the interpretation of lactate or base excess. Delayed sampling from unclamped cords is very unreliable.